Managing Customer Success: An Evolutionary Process Model for Role Development in SaaS Entrepreneurial Ventures - Lennart Jayasuriya (Junior Management Science (JUMS), 2023)
In an increasingly SaaS-driven, competitive entrepreneurial ecosystem, retaining customers has become a key challenge to solve for entrepreneurial ventures. Customer success management provides a possible response to this challenge, looking to build a close relationship with customers to ensure a maximum value-added through the sold software solution. This thesis conducts inductive qualitative research based on eight German SaaS entrepreneurial ventures. It showcases the evolution of the customer success management role in three phases from a 360° support towards a trusted advisor. Over three phases, task change from an operational to a more strategic focus, which is connected to changes in the internal collaboration. The results suggest a strong individual impulse to be a necessary condition for customer success management to emerge and evolve. Furthermore, the role development is accompanied by a perspective shift of the own entrepreneurial venture and a continuously iterating definition of customer success. The findings of this thesis highlight important challenges over the course of establishing a customer success management department in an entrepreneurial venture looking to provide theoretical groundwork for future research as well as start-ups investigating the topic.
Keywords: 650; Customer success management; Entrepreneurial ventures; Process model; SaaS; Grounded theory